Synthesis Monitoring, Characterization and Cleanup of Ag-Polydopamine Nanoparticles Used as Antibacterial Agents with Field-Flow Fractionation - Valentina Marassi; Sonia Casolari; Silvia Panzavolta; Francesca Bonvicini; Giovanna Angela Gentilomi; Stefano Giordani; Andrea Zattoni; Pierluigi Reschiglian; Barbara Roda (Antibiotics, 2022)
Advances in nanotechnology have opened up new horizons in nanomedicine through the synthesis of new composite nanomaterials able to tackle the growing drug resistance in bacterial strains. Among these, nanosilver antimicrobials sow promise for use in the treatment of bacterial infections. The use of polydopamine (PDA) as a biocompatible carrier for nanosilver is appealing; however, the synthesis and functionalization steps used to obtain Ag-PDA nanoparticles (NPs) are complex and require time-consuming cleanup processes. Post-synthesis treatment can also hinder the stability and applicability of the material, and dry, offline characterization is time-consuming and unrepresentative of real conditions. The optimization of Ag-PDA preparation and purification together with well-defined characterization are fundamental goals for the safe development of these new nanomaterials. In this paper, we show the use of field-flow fractionation with multi-angle light scattering and spectrophotometric detection to improve the synthesis and quality control of the production of Ag-PDA NPs. An ad hoc method was able to monitor particle growth in a TLC-like fashion; characterize the species obtained; and provide purified, isolated Ag-PDA nanoparticles, which proved to be biologically active as antibacterial agents, while achieving a short analysis time and being based on the use of green, cost-effective carriers such as water.